2021
DOI: 10.1002/jsfa.11301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of indoor, greenhouse, and field cultivation on bioactive compounds from parsley and basil

Abstract: BACKGROUND: Aromatic herbs are an important source of bioactive compounds. Different cultivation systems should give each plant a specific amount of those compounds, which should be of a particular quality. In this study, the effects of three cultivation systems (indoor, greenhouse, and organic field) on the composition of bioactive compounds in parsley (Petroselinum crispum cv. 'Flat Leaf'), green basil (Ocimum basilicum var. minimum cv. 'Greek'), and purple basil (Ocimum basilicum cv. 'Red Rubin') were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The results showed that the carotenoid content was determined genetically in basil cultivation with the purple genotype displaying a higher carotenoid content. The carotenoid content levels observed in this study for green basil are consistent with the values reported by Naznin et al [48] in green lemon basil and are lower compared to those reported by Proz et al [49] or both green and purple basil grown indoors, in a greenhouse or in open field. Moreover, in contrast with our results, Proz et al [49] reported higher total carotenoid content in green basil than in purple basil.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that the carotenoid content was determined genetically in basil cultivation with the purple genotype displaying a higher carotenoid content. The carotenoid content levels observed in this study for green basil are consistent with the values reported by Naznin et al [48] in green lemon basil and are lower compared to those reported by Proz et al [49] or both green and purple basil grown indoors, in a greenhouse or in open field. Moreover, in contrast with our results, Proz et al [49] reported higher total carotenoid content in green basil than in purple basil.…”
Section: Discussionsupporting
confidence: 92%
“…This plant's roots and leaves are used for spice purposes, mainly due to the content of valuable essential oils [11]. The content of essential oils in parsley roots and leaves depends on many factors, of which the cultivar and growing conditions are often mentioned [5,7,10,11,[13][14][15][16][17]38]. In this experiment, the content of the essential oils in the parsley roots was from 0.013 to 0.045 mL 100 g −1 FW, and was within the lower limits of the content given by other authors [5,8,18].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the predominance of apigenin derivatives, other flavonoids can be found in polar extracts of parsley aerial parts and/or leaves, such as glycosides of luteolin, diosmetin, kaempferol, quercetin, and isorhamnetin. Phenolic acids, coumarins, and coumaric acid derivatives are also frequently reported [35][36][37][38]40,41,46]. Table 1 summarizes the secondary metabolites identified in these extracts.…”
Section: Chemical Composition Of Parsley Extractsmentioning
confidence: 99%